Fatty acid, amino acid and vitamin composition of indian catfish, magur (Clarias batrachus) and singhi (Heteropneustes fossilis) (SAARC Journal of Agriculture, 2017)
The fatty acid, amino acid and fat soluble vitamin content of magur (Clarias batrachus) and singhi (Heteropneustes fossilis) were assayed from collected samples from different geographical locations. Length and weight of collected samples were (50-235g and 165-300 mm) for magur and (50-210g and 190-255mm) for singhi. The essential amino acid (EAA) and the non-essential amino acid (NEAA) content in magur and singhi did not differ significantly. The Vitamin A and D contents were significantly (P